THE REPRESENTATION OF AHMADIYAH’S CASE ON THE JAKARTA POST (A STUDY OF CRITICAL DISCOURSE ANALYSIS) - Kurnia, Hamdan (Journal of English Language and Literature Teaching, 2023)
This research is entitled “The Representation of Ahmadiyah’s Case on The Jakarta Post (A Study of Critical Discourse Analysis)”. This study discusses about the elements and the strategies that are used by Jakarta Post in writing the people that involve in Ahmadiyah’s case, and in what way Jakarta Post represent Ahmadiyah’s case. This research uses analytical descriptive method in analyzing the data. Here the data is collected, described, analyzed and made a conclusion. After analyzing the data, it is found that in writing the actor that involves in Ahmadiyah’s case, Jakarta Post uses two strategies: Passivization and Nominalization. The functions of those strategies are to hide the acts of the actor that involves in Ahmadiyah’s case like the government, the people and group that support Ahmadiyah, and the group that is against Ahmadiyah. The result also reveals that the largest number of using passivization and nominalization that are used by Jakarta Post in hiding the actor that are involving in Ahmadiyah’s case refers to the Government. By this strategies, the governments as the actor that is hidden by Jakarta Post is safe from the accusation of the society because of their decision in making the recommendation to ban Ahmadiyah.